The (non-)Keynesian effects of fiscal austerity: New evidence from a large sample - Afonso, António (2022)
We empirically assess whether the negative response of private consumption and private investment to fiscal consolidation usually expected is reversed. We focus on a sample of 174 countries between 1970 and 2018 to determine episodes of fiscal consolidations using three alternative measures of the cyclically adjusted primary balance: (1) an International Monetary Fund (IMF)-World Economic Outlook (WEO) based measure, (2) a Hodrick-Prescott–based measure, and (3) a measure based on Hamilton (2018). We find that, first, increases in government consumption have a Keynesian effect on real per capita private consumption; second, tax increases have a positive effect on private consumption when a fiscal consolidation occurs; and, third, fiscal contraction has a crowding-in effect on private investment. Moreover, expansionary fiscal consolidations occur in highly indebted advanced economies, in particular, after an increase in taxes. We conclude that the negative effects of taxation on private consumption are larger when developing economies are experiencing a financial crisis and are not consolidating.